2018
DOI: 10.2147/ijn.s167793
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun silver ion-loaded calcium phosphate/chitosan antibacterial composite fibrous membranes for guided bone regeneration

Abstract: PurposeThe purpose of this study is to construct a guided bone regeneration membrane that is similar to bone components and structurally resembles the native extracellular matrix with sufficient antibacterial properties.Materials and methodsA novel type of biomimetic and bioactive silver ion-loaded calcium phosphate/chitosan (Ag-CaP/CS) membrane with antibacterial ability was successfully developed by incorporation of silver ion-loaded CaP via a one-step electrospinning method and subsequently crosslinked with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 52 publications
(58 reference statements)
0
53
0
1
Order By: Relevance
“…The fibrous scaffolds are produced by application of high voltage over a polymer solution during a spinning process, and the scaffolds can provide suitable and beneficial surroundings for cell attachment and proliferation because of the similarity to the natural ECM architecture. 4 6 Various studies have revealed that electrospun scaffolds enhance the engraftment rate, 7 cellular organization, 4 , 8 and wound contraction 7 , 9 compared with porous scaffolds with micron-sized pores.…”
Section: Introductionmentioning
confidence: 99%
“…The fibrous scaffolds are produced by application of high voltage over a polymer solution during a spinning process, and the scaffolds can provide suitable and beneficial surroundings for cell attachment and proliferation because of the similarity to the natural ECM architecture. 4 6 Various studies have revealed that electrospun scaffolds enhance the engraftment rate, 7 cellular organization, 4 , 8 and wound contraction 7 , 9 compared with porous scaffolds with micron-sized pores.…”
Section: Introductionmentioning
confidence: 99%
“…After the addition of CaP, the surface of CaP/CS nano¯bers becomes rougher than CS¯bers. 58 The diameter of bers was with a broad range from 0 to 1000 nm. Serried Porphyromonas gingivalis bacteria attached to the CS and CaP/CS¯bers.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…The use of Guided Tissue/Bone Regeneration (GTR/GBR) approaches has recently increased in the oral and maxillofacial fields, being widely used for the augmentation of alveolar bone in maxillofacial surgery or in the reconstruction of oral tissues such as during the placement of dental implants, or during the regeneration of periodontal and endodontic tissues. This procedure is based on the concept of employing a physical barrier (membrane) to exclude gingival epithelium and connective tissue ingrowth, while enhancing the formation of bone and/or periodontal tissues [26][27][28][29][30]. Regarding their design, different polymeric materials have been employed for GTR/GBR including synthetic polymers like polytetrafluorethylene (PTFE) or aliphatic polyesters such as PLA, polygalacturonic acid (PGA) or PCL; and natural ones like collagen or alginate [26,31,32].…”
Section: Membranes For Guided Tissue/bone Regenerationmentioning
confidence: 99%
“…On the other hand, chitosan has been widely employed for GBR membranes blended with other natural polymers such as collagen, against S. mutans [42], and PCL and gelatin, against Escherichia coli and Staphylococcus aureus (Figure 1) [37]. As an alternative, Jin et al recently studied a composite-membrane combining chitosan and silver particles, which they hypothesized it could release silver ions from the fibers in a controlled manner in order to achieve enough antibacterial effects without affecting the biocompatibility of the material [30,30,43]. In the work carried out by Saarani et al, they described a triple-layered GBR membrane composed of poly(lactic-co-glycolic) acid (PLGA), nanoapatite and lauric acid [44].…”
Section: Membranes For Guided Tissue/bone Regenerationmentioning
confidence: 99%